Proterozoic - basal Cambrian stratigraphy across Nares Strait: correlation between Inglefield Land and Bache Peninsula - Peel, John S.; Dawes, Peter R.; Collinson, John D.; L. Christie, Robert (Meddelelser om Grønland. Geoscience, 2023)
In the Kane Basin region of Nares Strait (78° to 79°N) unmetamorphosed Proterozoic and basal Cambrian platform strata overlie the Precambrian Shield both in Inglefield Land in Greenland, and on Bache Peninsula in Ellesmere Island. The platform succession is composed of two shallow-water elastic sequences separated by an erosional disconformity. The lower formation, of multicoloured sandstone and siltstone with minor shale and stromatolitic dolomite, is assigned to the redefined Rensselaer Bay Formation; the upper, composed of red and overlying white sandstone with dolomitic sandstone and siltstone at the top, is assigned to the Dallas Bugt Formation. Basic sills from the Rensselaer Bay Formation have yielded isotopic ages as old as 1200 m.y., while the trace fossils Rusophycus and Skolithos suggest a basal Cambrian age for the Dallas Bugt Formation. The platform sequences of Inglefield Land and Bache Peninsula show striking similarity in lithology and thickness and the detail correlation is supported by the evidence from isotopic ages of basic sills and from trace fossils. In both areas the bipartite succession is overlain with apparent conformity by dolomites that pass upwards into limestones containing Early Cambrian macrofauna. The Rensselaer Bay Formation thickens southwards and passes into the much thicker sedimentary sequence of the Thule Basin, while the Dallas Bugt Formation and the overlying dolomites thicken northwards, indicating that the two formations were laid down in separate sedimentary basins. The close correlation of the platform successions and the corresponding configuration of the depositional slopes on both sides of the Kane Basin clearly indicate that the Proterozoic - Early Cambrian sedimentary pattern has not been radically disturbed by tectonism or by any appreciable transcurrent movement along Nares Strait.